Pengaruh Value Proposition Dan Level Of Loyalty Terhadap Keputusan Penggunaan Transportasi In-Driver Di Medan Timur - Pasaribu, Josua; Manalu, Darma; Tobing, Artha Lumban (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research aims to identify and analyze the main factors that influence customer loyalty in the highly competitive online transportation business. Transportation has an important role in everyday life, both in urban and rural areas. Of the various types of transportation, land transportation is the most dominant in Indonesia because of its accessibility, more affordable prices and flexibility. One of the online transportation companies developing in Indonesia is In-Driver, which entered the Indonesian market in 2019 with a unique feature in the form of a negotiation system between drivers and users. In tight competition with other online transportation services such as Gojek, Grab, and Maxim, In-Driver needs to pay attention to factors that influence customer loyalty, brand image, and the value perceived by customers.